Safety, feasibility and performance of Valvosoft non-invasive ultrasound therapy in patients with severe symptomatic calcific aortic valve stenosis. First-in-Man. (25th November 2020) - Messas, E; Ijsselmuiden, A; Goudot, G; Vlieger, S; Den Heijer, P; Puymirat, E; Spaulding, C; Zarka, S; Hagege, A.A; Marijon, E; Tanter, M; Bertrand, B; et al.
Abstract: Objectives: We recently developed a unique transthoracic non-invasive ultrasound therapy device called Valvosoft to treat aortic stenosis. The therapy consists in delivering trans-thoracically precisely focused and controlled short ultrasound pulses (<20μsec) at a high acoustic intensity to produce non-thermal mechanical tissue softening of the calcified aortic valve with the ultimate aim of improving the valve opening. Ultrasound imaging enables to follow valve movements in real-time and thus targets the ultrasound waves on the valve with great precision. After having validated this concept in pre-clinical studies, we aimed at applying this technique in human. The primary objectives were to assess the safety and feasibility of this novel technique along with its performance by evaluation of the valve leaflets mobility and valve opening area. Methods: This is a multi-center, prospective, controlled first-in-man study. Ten patients with severe symptomatic calcific aortic stenosis and not eligible for SAVR/TAVR underwent a Valvosoft ultrasound therapy. The therapy consists of 6 sessions of ultrasound therapy. The Valvosoft transducer is applied on the patient's chest and coupled at its center with an echocardiography phased array probe to allow real-time control of the therapy (cavitation bubble detection). Preselection of the region of interest is performed by echo still frame before each session. Ultrasonic evaluation was performed by an independent core lab at baseline, discharge, 30-day and 3 month follow-up along with clinical follow up. Results: Enrolled patients were advanced in age (84.1±6.5 yrs) with severe comorbidities (8 with heart failure, 5 with coronary heart disease and 5 with kidney failure). All had extensive aortic valve calcification (mean calcification volume of 687.28 mm 3 ) with mean AVA of 0.61±0.17 cm 2 and mean pressure gradient of 37.5±10.5 mmHg (6 patients had SV<35ml/m 2 ). No adverse events were recorded during the procedures other than some benign ventricular extrasystoles. The mean treatment time was 52 minutes. At 3 months follow-up, one patient had died due to end stage heart failure not linked to the procedure (9 weeks post procedure) and another got finally TAVI (45 days post procedure). Of the other 8 patients, 6 experienced an improvement of their NYHA status. No device or procedure related major adverse events nor deterioration of neurological status were observed at 3 months follow-up. Of the 7 patients that had echo follow-up at 3 months (one patient refused to get echo evaluation), 5 increased the AVA (between 14% and 46%) and 4 patients decreased the mean pressure gradient (from 6% to 44%). No AI or EF deterioration occurred during follow up. Conclusion: Non-invasive ultrasound therapy is feasible and safe in patients with severe aortic valve stenosis and is able to improve AVA and pressure gradient in some patient. Larger studies with longer follow up will need to be conducted. Funding Acknowledgement: Type of funding source: Private grant(s) and/or Sponsorship. Main funding source(s): Cardiawave SA, Paris, France